2018
DOI: 10.1126/scitranslmed.aat8410
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-host disease, but not graft-versus-leukemia immunity, is mediated by GM-CSF–licensed myeloid cells

Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) not only is an effective treatment for several hematologic malignancies but can also result in potentially life-threatening graft-versus-host disease (GvHD). GvHD is caused by T cells within the allograft attacking nonmalignant host tissues; however, these same T cells mediate the therapeutic graft-versus-leukemia (GvL) response. Thus, there is an urgent need to understand how to mechanistically uncouple GvL from GvHD. Using preclinical models of full an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 46 publications
3
73
0
Order By: Relevance
“…Where they have been isolated from primary human tissues, their function has been described as regulatory, in comparison with DC (33,34). Our findings that GVHD macrophages have functional attributes capable of promoting GVHD provide an important corroboration of recent mouse models describing the dependence of GVHD pathology upon donor myeloid cells activated by T cell-derived GM-CSF (19).…”
Section: Myeloid Cells Found In Gvhd Have Previously Been Characterizsupporting
confidence: 79%
See 2 more Smart Citations
“…Where they have been isolated from primary human tissues, their function has been described as regulatory, in comparison with DC (33,34). Our findings that GVHD macrophages have functional attributes capable of promoting GVHD provide an important corroboration of recent mouse models describing the dependence of GVHD pathology upon donor myeloid cells activated by T cell-derived GM-CSF (19).…”
Section: Myeloid Cells Found In Gvhd Have Previously Been Characterizsupporting
confidence: 79%
“…Unlike T cells in the human adult, which may take more than 2 years to recover after transplantation, myeloid cells are continuously generated, and rapid immune reconstitution is possible following myeloid-targeted interventions. The ability to isolate discrete mechanisms that govern the infiltration of tissues by myeloid cells, such as GM-CSF dependence, may also offer a means of minimising GVHD without compromising GVL (19).…”
Section: Gvhd Macrophages Demonstrated Enhanced T Cell Stimulatory Fumentioning
confidence: 99%
See 1 more Smart Citation
“…In graft-versus-host disease, high GM-CSF produced by allogeneic T cells induces donorderived myeloid cells to produce inflammatory cytokines, which drives pathology 74 . In hepatocellular carcinoma, tumor cells produce high amounts of GM-CSF that recruit myeloid derived suppressor cells to induce immune tolerance and increase PD-L1 expression 75 .…”
Section: Gm-csf Production By T Cells Activates Myeloid Cells For Infmentioning
confidence: 99%
“…By using a light inducible photo‐converter system it was shown that neutrophils that were photo‐converted in the terminal ileum were later detected in the mesenteric lymph nodes. Granulocyte‐macrophage colony‐stimulating factor drives GVHD pathology by licensing donor‐derived myeloid phagocytic cells to produce inflammatory mediators, such as interleukin (IL) 1β and ROS and promote GVHD (Tugues et al , ).…”
Section: Early Tissue Damage and Innate Immune Cells In Gvhdmentioning
confidence: 99%